Pim Higginson. Scoring Race: Jazz, Fiction, and Francophone Africa. James Currey, 2017. - Van Kelly (Studies in 20th & 21st Century Literature, 2018)
Review of Pim Higginson. Scoring Race: Jazz, Fiction, and Francophone Africa. James Currey, 2017.
Keywords: Review; Higginson; Jazz